Pelaksanaan Ketentuan Pasal 15 Ayat (2) Huruf B Undang-Undang Nomor 11 Tahun 2016 Tentang Pengampunan Pajak - I Dewa Ayu Werdiyani (Fakultas Hukum Universitas Mataram, 2017)
The purpose of this study is to analyze the implementation of the provisions of Article 15 paragraph (2) Letter b of Act Number 11 Year 2016 on Tax Amnesty. The Tax Amnesty is a Government program as regulated in Act Number 11 Year 2016 concerning Tax Remissions that the abolition of taxes that should be payable for income tax is not subject to tax administration sanctions or criminal sanctions in the field of taxation by disclosing property and paying ransom. Disclosure of property carried out by the taxpayer using Statement Letter containing debt, net worth, and calculation and payment of ransom including property in the form of moving objects or immovable objects that have been reversed name on behalf of the taxpayer and who have not reversed the name of the taxpayer's. Specificallyfor Statement Letter on immovable objects in the form of land and / or building who have not reversed the name of taxpayer's must be with Statement Certificate legalized by Notary as stipulated in Article 15 Paragraph (2) Letter b of Act Number 11 Year 2016 concerning Tax Amnesty. In practice, the provisions of this article have not been properly implemented.